Penggunaan Abu Cangkang Siput Sebagai Filler Pada Lapisan Asphalt AC-BC - Edito Dwi Antoro (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
Abstract The snail shell in the Bai Island Region of Bengkulu City is very large, if we don't use it offensively it will disturb the surrounding environment because it is left scattered on the riverbank. As for the efforts to utilize this waste, one of which is the most likely one we can use is the use of this snail shell for replacing fillers in the Asphalt Concrete Binder Course (AC-BC) mixture. The purpose of this research is to determine the characteristics of a mixture of AC-BC layers with fillers from snail shell ash waste in the Bai Island area of ??Bengkulu City, while the parameters used are as follows: Stability, Flow, Marshall Quotient, cavities in the mixture (VIM), intermediate cavity (VMA), asphalt filled cavity (VFA) and evaluate the performance of the mixture against the specifications required for AC-BC coated concrete mixtures. The results obtained stability value of 0% snail shell ash is 1036.3 kg. The stability value using snail fly ash 50% 964.8 kg. The stability value of snail shell ash is 100% 880.9 kg. While the flow in the mixture of 0% snail fly ash is 3.4 mm. The flow value of 50% snail shell ash is 3.7 mm and 100% flow of snail shell ash is 3.3 mm. From this research, obtained by using snail shell ash shows that the value of stability has decreased with the increasing number of snail shell ash but still fulfills the requirements of the 2010 General Highways specifications with a requirement value of> 800 kg. The flow value also shows that the mixture meets the requirements of the 2010 Bina Marga General specifications with a requirement value of> 3 mm, although the flow value has decreased, but in 50% of snail shell ash the flow value has increased by 3.7 mm.